Challenging Problems of Education of Qualified Teachers Today - Komilovna, Hotamova Dildora (European Journal of Life Safety and Stability (2660-9630), 2022)
In the process of professional practice in higher education institutions, future specialists learn ways to independently and creatively apply theoretical knowledge relevant to their profession, acquire professional skills, observe and analyze children’s development, and evaluate the level of knowledge. Children learn to organize various activities, plan educational and educational work. In this article, we teach how to train pedagogues in quality, how to conduct excellent explanations in the course of the lesson.